Yearbook of the European Convention on Human Rights/Annuaire de la convention europeenne des droits de l'homme, Volume 49 (2006) (Human Rights and Humanitarian Law - Book Archive 2000-2005., 2007)
The Yearbook of the European Convention on Human Rights, edited by staff of the Council of Europe, is an indispensable record of the development and impact of the world's oldest binding international human rights treaty. It reviews the implementation of the Convention both by the European Court of Human Rights and in national legislation and practice. The Yearbook includes: Full text of any new protocols to the Convention as they are opened for signature, together with the state of signatures and ratifications. Full listing of Court judgments; judgments broken down by subject-matter; and extensive summaries of key judgments handed down by the Court during the year. Selected human rights (DH) resolutions adopted as part of the Committee of Ministers' work supervising the execution of the Court's judgments. Enquiries by the Secretary General carried out under Article 52 of the Convention. Other work of the Council of Europe connected with the European Convention on Human Rights, carried out by the Committee of Ministers, the Parliamentary Assembly, and the Directorate General of Human Rights. A summary survey of the implementation in certain member states of the Convention in the form of both legislation and case-law. Bibliographic information from the library of the European Court of Human Rights. The Yearbook is published in an English-French bilingual edition.